Bone and muscle geometry in female adolescent middle-distance runners - Greene, D.; Naughton, G. A.; Briody, J. N.; Kemp, A.; Woodhead, H.; Farpour-Lambert, N. (Pediatric Exercise Science, 2005)
This study compared tibial bone and muscle geometry and total body and regional bone mineral content (BMC) in elite female adolescent middle-distance runners (n = 20, age: 16 ± 1.7 years) and age- and sex-matched controls (n = 20, 16 ± 1.8 years) using magnetic resonance imaging and dual-energy X-ray absorptiometry. Significant advantages were found in athletes compared with controls in bone and muscle geometric values for distal tibial cortical, medullary cavity, distal tibial total muscle and dorsi flexor muscle compartment cross-sectional area, and regional BMC. Results imply mechanical loads associated with middle-distance running might be beneficial to musculoskeletal health in adolescent females.